Acute-onset heart failure secondary to biventricular non-compaction cardiomyopathy and atrial septal defect in a woman presenting in the seventh decade. Issue 2 (28th February 2022) - Sharma, Purva; Jobanputra, Yash; Chait, Robert; Ghumman, Waqas
Abstract : We present a case of a previously asymptomatic 63-year-old woman who presented with worsening dyspnoea for 3 weeks. Initial transthoracic and later transoesophageal echocardiography confirmed biventricular non-compaction cardiomyopathy and a large secundum atrial septal defect (ASD) measuring 1.4 cm. Additionally, there was a haemodynamically significant left to right shunt causing acute decompensated systolic heart failure. She eventually underwent closure of the septal defect using a AMPLATZER Septal Occluder device. Decision to close the defect was made as the left to right shunt was causing severe pulmonary hypertension and acute heart failure. Since most heart failure treatments involve lowering of the LV afterload there was consideration that this could cause right to left shunting and could cause an Eisenmenger physiology. Hence the AMPLATZER Septal Occluder device was placed to eliminate the shunt through the ASD. The ASD combined with the non-compaction posed significant treatment challenge in this case.